2017
DOI: 10.1063/1.4975613
|View full text |Cite
|
Sign up to set email alerts
|

Generation of 20 kA electron beam from a laser wakefield accelerator

Abstract: We present the experimentally generated electron bunch from laser-wakefield acceleration (LWFA) with a charge of 620 pC and a maximum energy up to 0.6 GeV by irradiating 80 TW laser pulses at a 3 mm Helium gas jet. The charge of injected electrons is much larger than the normal scaling laws of LWFA in bubble regime. We also got a quasi-monoenergetic electron beam with energy peaked at 249 MeV and a charge of 68 pC with the similar laser conditions but lower plasma density. As confirmed by 2D particle-in-cell s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…Scaling the charge to the nanocoulomb range following original predictions 15 would yield hundreds of kiloamperes peak-current beams, the key component for next-generation compact light sources. During the submission of this manuscript, Li et al 20 demonstrated generation of electron beams up to 20 kA from laser wakefield acceleration yet of a continuous spectrum extending up to 0.6 GeV. Laser-plasma accelerators generating such high currents accumulate enough charge such that the self-fields of the bunch will superimpose on the wakefield 21 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Scaling the charge to the nanocoulomb range following original predictions 15 would yield hundreds of kiloamperes peak-current beams, the key component for next-generation compact light sources. During the submission of this manuscript, Li et al 20 demonstrated generation of electron beams up to 20 kA from laser wakefield acceleration yet of a continuous spectrum extending up to 0.6 GeV. Laser-plasma accelerators generating such high currents accumulate enough charge such that the self-fields of the bunch will superimpose on the wakefield 21 23 .…”
Section: Introductionmentioning
confidence: 99%
“…For the preservation of low normalized bunch emittance values as regarded here (ε n ¼ 0.2 mm mrad) [92], space-charge effects arising from large bunch charges [93] should be avoided. To circumvent this effect, a sufficiently low bunch charge of Q ¼ 10 pC was chosen for the simulations, an amount easily achievable by today's laser-plasma accelerators [94][95][96].…”
Section: Design Resultsmentioning
confidence: 99%
“…of quasi-monoenergetic peak of electrons from bubble-regime LWFAs versus (a) peak energy Ee, and (b) charge Q within the peak, from 21 experiments using electron injection methods depicted schematically in right-hand column: selfinjection, filled gold circles (Faure et al, 2004;Gallacher et al, 2009;Kim et al, 2013a;Kneip et al, 2009;Leemans et al, 2006;Li et al, 2017;Mangles et al, 2004;Osterhoff et al, 2008;Wang et al, 2013); colliding pulses, green stars (Faure et al, 2006;Rechatin et al, 2009); single shock-induced density ramp, filled blue squares (Buck et al, 2013;Khrennikov et al, 2015a;Schmid et al, 2010;Swanson et al, 2017); tailored multi-ramp, open black (Gonsalves et al, 2011) and filled black (Wang et al, 2016) triangles;ionization-induced, open red (McGuffey et al, 2010;Pak et al, 2010) and filled red (Couperus et al, 2017;Mirzaie et al, 2015;Pollock et al, 2011) diamonds. Plotted ∆E…”
Section: Charge and Energy Spreadmentioning
confidence: 99%